Aplikasi Sistem Informasi Geografis untuk Analisis Sifat Fisik Tanah untuk Lahan Pertanian Padi di Wilayah Penyangga Ibu Kota Kota Nusantara - Brillyansyah, Degita Fahmi; Alfarizi, Muhammad Ihsan; Mualimin, Lulus; Hita, Muhammad Arga; Jaya, Gigieh Henggar (Program Studi Teknik Pertanian, Fakultas Pertanian, Universitas Jenderal Soedirman, 2025)
The relocation of the national capital from the Special Region of Jakarta to the Capital City Nusantara (IKN) in East Kalimantan poses strategic challenges in agriculture, particularly food availability. Population migration to IKN will significantly increase food demand, while the land characteristics in East Kalimantan, which are dominated by peat ecosystems and plantations, pose serious challenges for the development of rice farming. The imbalance between increased demand and limited local production potential risks food insecurity if not anticipated. This study aims to analyze the potential of land resources in two IKN buffer zones, namely Paser District and Penajam Paser Utara District, as food supply areas. The research method uses a Geographic Information System (GIS) approach with overlay techniques to identify potential zones for rice farming development. Analysis was conducted based on land suitability parameters including: Soil type, soil texture, moisture content, and porosity. The results showed that there are several areas with the potential to be developed as rice farming land. The results of this study are expected to be a scientific basis for the formulation of policies for the development of sustainable rice farming areas and meeting food needs in IKN.